Early medieval miniature axes of Makarov’s type 2 in the Baltic Sea Region - Kucypera, Paweł; Wadyl, Sławomir (Archaeologia Lituana, 2011)
Artefacts which are miniatures of regular size objects met a thorough interest in the archaeological literature. Unsurprisingly, several attempts to interpret phenomenon of the miniature axes have already been made (see. eg. Kucypera, Pranke, Wadyl, 2010 a; Kucypera, Pranke, Wadyl, 2010 b; Wołoszyn, 2006; Panasiewicz, Wołoszyn, 2002; Zemītis, 1998; Koktvedgaard Zeitzen, 1997; Golubeva, 1997; Makarov, 1992; Darkevič, 1961; Paulsen, 1956; Paulsen, 1939). It should be noticed that miniatures are defined as objects reduced in size to an extent preventing their practical application, which distinguishes them from tools smaller than typical, but which still may perform functions similar to those of a normal-sized examples. Despite this, defining a miniature object creates many difficulties. M. Koktvedgaard Zeitzen recently wrote that: “Instead, one should take into account how the axe looks – whether, for example, it is ornamented or has a suspension hole – which, although a more subjective criterion, seem to give one a better basis for identifying an amuletic axe than solely measuring its length in centimeters. Another way to identify amuletic axes is to look at their material <…>” (Koktvedgaard Zeitzen, 1997, p. 16). We fully share this view. [...]